Underappreciated Utility of the Purse-String Suture in Head and Neck Skin Cancer Defect Reconstruction. Issue 2 (February 2019) - Collett, Tolbin; Smith, Andrea; Liu, Yuan F.; Bradford, Benjamin; Yang, Jin; Ardeshirpour, Farhad; Inman, Jared C.
Abstract : BACKGROUND: The purse-string suture (PSS) is a simple, reversible method for reconstructing skin cancer defects. Its utility may be underappreciated in head and neck reconstructive surgery. OBJECTIVE: To evaluate the utility of the PSS as an adjunct to the reconstructive ladder when reconstructing head and neck skin cancer defects. MATERIALS AND METHODS: This prospective nonrandomized cohort included 109 consecutive adult patients with head and neck defects resulting from skin cancer resection. The PSS was placed in every patient after resection. Patients were evaluated before and after suture placement, and final reconstructive methods were recorded. RESULTS: The PSS resulted in a mean defect area reduction of 77.1% ( p < .001) and was used in the final reconstruction in 79 (72.5%) patients. The PSS reduced the number of patients requiring adjacent tissue transfer (11), regional tissue transfer (3), and free tissue transfer (1) by 69.4%, 70%, and 80%, respectively. Fifty patients underwent reconstruction in the operating room. After intraoperative placement of the PSS, it was determined that 22 (44.0%) of these defects could have been reconstructed in the clinic ( p = .003). CONCLUSION: The PSS dramatically reduces defect size, simplifies reconstructive techniques, and often permits reconstruction to be performed in the clinic rather than the operating room.